Giant condyloma acuminatum: case report - Ganem, Natasha S.; Silva, Beatriz C.; Nascimento, Maria L.F.O.; Tibúrcio, Alberto Saraiva; Motta, Leonardo P.; Lyra, Marcelo R.; Lyra, Marcelo R.; Mesquita, Rodrigo B.; Gama, Júlio A.C.; Almeida, Mônica S. (Brazilian Journal of Sexually Transmitted Diseases, 2010)
Introduction: Buschke-Löwenstein tumor is an uncommon variety of HPV infection. Being histologically benign, the tumor has invasive behavior. It may be associated with conditions of immunosupression, and recurrence after treatment is frequent. Objective: to describe a case in a patient with AIDS, to show that immunosupression is a contributing factor, and that surgery is the most effective treatment. Methods: a case description, with references in the literature. Results: extended resection surgery with satisfactory outcome in the postoperative period. Conclusion: surgery is the treatment recommended by most authors and biopsy is an indicative procedure to exclude malignancy.